2007
DOI: 10.1007/s00436-007-0482-2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of an adult worm “vomit” preparation of Schistosoma mansoni and its potential use as antigen for diagnosis

Abstract: Schistosoma mansoni is a parasitic trematode of the portal-mesenteric veins with a closed-end intestine. Adult worms regurgitate their intestinal content after digestion, together with constituents of the lining gut. Some of these molecules circulate in the blood and are antigenic. We obtain a "vomit" preparation and preliminary evaluate its biochemical composition and antigenic capacity. The "vomit" preparation was obtained after changes in temperature and solutions of incubation of adult worms between 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…The present results clearly demonstrated that CS sensitivity to detect IgG in plasma of S. mansoni infected mice was generally higher than that of WoV which contrasted the previous study that compared the sensitivity of the two antigens to detect IgG in sera of infected humans residing in an endemic area in Burkina Faso [15]. Furthermore, antibodies against certain antigens present in the worm intestine, may take longer time to disappear [24].…”
Section: Discussioncontrasting
confidence: 53%
“…The present results clearly demonstrated that CS sensitivity to detect IgG in plasma of S. mansoni infected mice was generally higher than that of WoV which contrasted the previous study that compared the sensitivity of the two antigens to detect IgG in sera of infected humans residing in an endemic area in Burkina Faso [15]. Furthermore, antibodies against certain antigens present in the worm intestine, may take longer time to disappear [24].…”
Section: Discussioncontrasting
confidence: 53%
“…However, worms in vitro are rarely seen voiding Hz unless they are subjected to a chemical, osmotic, or temperature shock [11], [63], [64]. Indeed, the one direct series of observations on adult worms in the intestinal vasculature of mice [31] makes no mention of Hz regurgitation.…”
Section: Waste Disposalmentioning
confidence: 99%
“…Instead, intense motor activity in the anterior gut, followed by relaxation of the esophageal wall muscles, resulted in the movement of a thin dark line of vomitus up the esophageal lumen and out through the mouth [26] (Figure 3D). It is unclear whether Hz can be selectively eliminated during regurgitation, while important cathepsins, peptidases, saposins, and a variety of carrier protein homologs are retained [11], [63], [64]. However, the Hz expelled into the bloodstream of infected animals [65], [66] has been proposed to exert an immunomodulatory effect on the host [67].…”
Section: Waste Disposalmentioning
confidence: 99%
“…More recently, using microarray analysis, Gobert et al (2010) showed that genes encoding cathepsin B and cathepsin L were greatly up-regulated in S. mansoni larvae cultured for 5 days (65 and 37-fold, respectively). Both SmCBs and SmCLs are highly immunogenic in infected mice and antibodies are detected in sera of S. mansoni -infected patients (Dalton et al, 1995; Dalton and Brindley, 1996; Planchart et al, 2007; Sulbarán et al, 2010). …”
mentioning
confidence: 99%